Deregulation of selected microRNAs in sinonasal carcinoma: Value of miR‐21 as prognostic biomarker in sinonasal squamous cell carcinoma. Issue 12 (28th September 2017) - Kovarikova, Helena; Bubancova, Ivana; Laco, Jan; Sieglova, Katerina; Vosmikova, Hana; Vosmik, Milan; Dundr, Pavel; Nemejcova, Kristyna; Michalek, Jaroslav; Palicka, Vladimir; Chmelarova, Marcela
Abstract: Background: Tumors occurring in the sinonasal area are characterized by unfavorable outcome due to difficult diagnosis, treatment, and prognosis of the disease corresponding with the anatomic complexity of the area. Methods: We used quantitative real‐time polymerase chain reaction (PCR) to compare relative expression of miR‐21, miR‐141, and miR‐200c in 70 formalin‐fixed, paraffin‐embedded samples of sinonasal carcinoma tissue (majority of squamous cell carcinoma [SCC] samples) with 17 control samples of sinonasal tissue. Results: Our data showed significant upregulation of miR‐21 in sinonasal cancer tissue. Expression levels of miR‐141 and miR‐200c were below detectable levels in both sinonasal cancer samples and healthy tissue. Kaplan‐Meier analysis with log‐rank survival showed that patients with SCC with high expression of miR‐21 (highest quartile) had impaired survival close to reaching statistical significance ( P  = .0630). Conclusion: Our results suggest that miR‐21 upregulation is involved in tumorigenesis of sinonasal carcinoma and that it is associated with poor prognosis. Thus, miR‐21 could be used as a valuable prognostic biomarker.